(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
A number of scientific studies give reasons to assume that children raised and educated in the „Family-type accommodation center” need additional targeted activities to learn and improve the various activities of everyday life. The aim of the present study is to determine the impact of additional occupational therapy activities on the formation of skills for independent living in children raised and educated in social services. Scope of the study: there were studied 21 children aged 7 to 12 years, users of social services with the test „Formation of skills for independent living”. Test „Leisure Management”, the evaluation is on a 3-point scale. Statistical methods are Wilcoxon rank test, t-test of Student. In the final results of the test in 80,95% of the examined children there was an improvement between 0,5 and 1 point, which is statistically significant on a 3-point scale. In the initial values of all groups of activities there is a slight difference (within 0,23), as the results are below the „average level” (2 points) in the skills for independent living. In the final measurements, the results are within 2,42; 2,38 for the second and third groups of activities and 2,08; 2,18 in the first and fourth groups of activities, which is more than the „average level”. Preparing for independent living is part of the overall process of working with children which are receiving social support. The good final results in the conducted research are due to the individual purposeful work on the implementation of the activities of the occupational therapy program for the formation of skills for independent living. The application of a set of activities for the formation of their skills for everyday life is a priority goal in the work of the responsible institutions and specialists for improving the quality of child care. The various and meaningful activities provided in their individual programs support the process of acquiring a set of knowledge and skills that they will need in the future independent life. The inclusion of appropriate occupational therapy activities for the formation of skills for independent living in children raised and educated in the „Family-type accommodation center” has a beneficial effect on the overall personal development and formation of social skills.